Using Transcranial Magnetic Stimulation to Evaluate the Motor Pathways After an Intraoperative Spinal Cord Injury and to Predict the Recovery of Intraoperative Transcranial Electrical Motor Evoked Potentials: A Case Report. Issue 3 (June 2016) - Grover, Helen J.; Thornton, Rachel; Lutchman, Lennel N.; Blake, Julian C.
Abstract : Summary: The authors report a case of unilateral loss of intraoperative transcranial electrical motor evoked potentials (TES MEP) associated with a spinal cord injury during scoliosis correction and the subsequent use of extraoperative transcranial magnetic stimulation to monitor the recovery of spinal cord function. The authors demonstrate the absence of TES MEPs and absent transcranial magnetic stimulation responses in the immediate postoperative period, and document the partial recovery of transcranial magnetic stimulation responses, which corresponded to partial recovery of TES MEPs. Intraoperative TES MEPs were enhanced using spatial facilitation technique, which enabled the patient to undergo further surgery to stabilize the spine and correct her scoliosis. This case report supports evidence of the use of extraoperative transcranial magnetic stimulation to predict the presence of intraoperative TES responses and demonstrates the usefulness of spatial facilitation to monitor TES MEPs in a patient with a preexisting spinal cord injury.